SOLVING CUTTING STOCK PROBLEM USING PATTERN GENERATION METHOD ON 2-DIMENSIONAL STOCK - Hasbiyati, Ihda; Latifa, Indri; Rahman, Abdul; Ahriyati, Ahriyati; Gamal, Moh Danil Hendry (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
This article discusses the solution of the 2-dimensional stock cutting problem using the Branch and Bound modified pattern generation method. The pattern generation method will produce a feasible cutting pattern matrix which is then converted into a mathematical model with a linear program equation with an objective function to minimize the use of initial stock materials. The research is a case study located at the Handal Karya Buana Store which is engaged in cutting glass of different sizes, thicknesses and types of glass. In this case, 3 types of initial stock will be used with the same thickness, and type but have different area sizes, and one of the consumer demand data will be used, namely 3 types of requests with different sizes and many requests. By using the pattern generator method, 10 cutting patterns are generated with each different cutting residue. By using the simplex method, the optimal solution is obtained for the amount of initial stock needed, the pattern used and the remaining cuts produced. So using the pattern generator method can produce a feasible cutting pattern, and can be used as an alternative to solve the stock cutting problem.